Utilization of Social Media Instagram @Diskominfo.Semarang as a Public Information Medium in Improving the Agency's Positive Image - Siti Rohmah; Alifa Nur Fitri (Journal Commedies, 2025)
Social media platforms such as Facebook, Twitter, Instagram, and LinkedIn allow users to interact with others, share information, and express themselves online. This research aims to determine the use of social media Instagram @Diskominfo.Semarang as a public information medium in improving the positive image of the agency. The method used in this research is a qualitative method using data collection techniques in the form of interviews, observation and documentation. This research refers to the theory of The Circular Model Of Some. The research results obtained are 1) Sharing before sharing content, namely forming an Instagram social media team, classifying the type of content, content in publishing content and carrying out layered verification 2) Optimize utilizing all features on Instagram, using language that is easy to understand, creating various types of content and publishing all activities 3) Manage the social media team well and use Instagram analytical features to analyze Instagram developments 4) Engage involves all social media, communication and PR teams and the public can submit complaints or opinions to the Semarang government via an account Instagram @kominfo.semarang.